Mountains of Europe - Bottoni, Luciana, 1952-; Fornasari, Lorenzo; Massa, Renato; Shubert, Mia (World nature encyclopedia, 1989)
Describes the geographical features, climate and plants and animals of the European mountains with emphasis on their interrelationship.